A SHEPWM Technique With Constant v/f for Multilevel Inverters - Tuncer, Servet; Tatar, Yetkin; Guldemir, Hanifi (Gazi Univ, 2005)
This paper concern on a new application of selected harmonic elimination pulse width modulation technique (SHEPWM) for multilevel inverters. In this paper, first, the switching angles are calculated using constrained optimization technique. With these switching angles both the fundamental harmonic can be controlled and the selected harmonics can be eliminated. Then, using these calculated switching angles, a set of equation is formed which calculates the switching angles with respect to modulation index. Using this technique three-phase voltage has been obtained from a five-level cascade inverter. This voltage is applied to an induction motor. The dynamic behaviour of the induction motor has been examined for constant v/f operation and the simulation results have been given.
Keywords: Multilevel inverter; SHEPWM technique; optimization theory; induction motor; v/f operation